Perfis sanitário e social da ovinocaprinocultura do oeste potiguar - Souza, Carlos Henrique de (Universidade Federal Rural do Semi-Árido, 2016)
The aim of this study was to describe the profile of the sheep and goat farmers in the West Potiguar region, through questionnaires that reveal the social characteristics of the creators and hygiene and health characteristics of goat and sheep herds. They were conducted 243 interviews with creators sheep and goat farmers of family farming, with flocks of up to 100 animals. After application of the questionnaires, was obtained a database, which indicated important characteristics, as well as weaknesses of the productive chain and possible risk factors of sanitary and hygienic management. The results showed that 85.0% and 81.2% of sheep and goat farmers respectively, reside in the property; 71.2% and 75.3% of sheep and goat farmers respectively, has the property as the only source of income; more than 75.0% of the farmers have not completed primary education, regardless of the analyzed species of herd. The predominant farming system is semi-extensive, the installations are predominantly of dirt floor pressed and the use of isolation of animals was not routine practice. The deworming is a common practice in 99.1% of sheep and 95.9% of goats herds, but is performed without any technical orientation, such as dosages and frequency. Among the deworming, clostridiums is the most applied between the breeders, and the goat herd with the immunization rate (60.6%) higher than the herd sheep (41.6%). The clinical signs more reported by sheep and goats breeders were respectively, diarrhea (88.5% and 88.8%), screwworm (81.4% and 79.4%), anemia (62.8% and 59.4% ), abortion (51.3% and 46.5%) and abscess (38.1% and 30%), only varying the proportion of the related cases. We conclude that the technical assistance and the participation in associations or cooperatives contributed to an increase in productivity and control of diseases in these herds
Keywords: Manejo sanitário; Semiárido; Pequenos ruminantes; produtividade; Health management; Semi-arid; Small ruminants; Productivity; CIENCIAS AGRARIAS::MEDICINA VETERINARIA